A Review Article on the Prediction of Diseases at an Early Stage (International Journal of Innovative Research in Computer Science & Technology, 2023)
Individuals today suffer from a wide range  of diseases as a result of their lifestyle choices and the  environment in which they live. The objective of  forecasting disease at an earlier stage becomes an  increasingly vital condition as the identification and  prediction of such diseases at their earlier phases become  highly significant. Most individuals are too lazy to go to  the hospital or see a doctor for a small problem. Our  approach focuses on accuracy to detect additional  symptoms for illness prediction in healthcare. In this  section, I've employed a variety of machine learning  algorithms carefully and focused in this few, which  achieved the highest accuracy with that specific condition  in order to build a strong model that produces the most  exact forecasts. This work introduces the topics of illness  prediction, disease therapy, and local medical consultation  with effective machine learning programming. There are  several diseases in the world that are brought on by the  conditions of people's living habits or their surroundings.  Thus, this study offers a summary of machine learning based illness prediction.
Keywords: Disease Prediction; Machine Learning; Healthcare; Random Forest